2006
DOI: 10.1525/mp.2006.24.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Groove Induced by Music: Consistency and Phenomenology

Abstract: There is a quality of music that makes people tap their feet, rock their head, and get up and dance. The consistency of this experience among listeners was examined, in terms of differences in ratings across 64 music examples taken from commercially available recordings. Results show that ratings of groove, operationally defined as “wanting to move some part of the body in relation to some aspect of the sound pattern,” exhibited considerable interindividual consistency. Covariance patterns among the 14 rated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(219 citation statements)
references
References 17 publications
11
205
3
Order By: Relevance
“…Madison (2006) asked nonmusicians to rate a large number of musical excerpts from different genres on 14 scales, one of which was labeled "groove," defined as "inducing movement." A factor analysis yielded four factors, one of which loaded highly on the "groove" and "driving" scales.…”
Section: The "Groove" Of Musicmentioning
confidence: 99%
“…Madison (2006) asked nonmusicians to rate a large number of musical excerpts from different genres on 14 scales, one of which was labeled "groove," defined as "inducing movement." A factor analysis yielded four factors, one of which loaded highly on the "groove" and "driving" scales.…”
Section: The "Groove" Of Musicmentioning
confidence: 99%
“…Indeed, a fascinating aspect of beat perception is its strong relationship with movement [45][46][47][48][49][50]. On the one hand, music spontaneously entrains humans to move [45][46][47]. On the other hand, it has been shown that movement influences the perception of musical rhythms [46,51].…”
Section: Neural Entrainment Underlying Sensorimotor Synchronization Tmentioning
confidence: 99%
“…Groove has a strong affective component, as well as a strong correlation to music appreciation (Madison, 2006). According to Janata et al (2012), we find pleasurable the music that makes us want to dance and such music elicits spontaneous rhythmic movements.…”
Section: Groove In the Literaturementioning
confidence: 95%
“…Based on the frequency of the words in the responses, they formed a definition: "groove is the aspect of the music that induces a pleasant sense of wanting to move along with the music" (p. 56). In the following, we adopted Madison's (2006) definition of groove: "the sensation of wanting to move some part of the body" (p. 203) in relation to some aspect of the sound pattern.…”
Section: Groove In the Literaturementioning
confidence: 99%